PTH-115 Increasing Access to Hepatitis C Treatment in The North East of England. (17th August 2016) - Welsh, S; Valappil, M; Miller, C; Robinson, E; Price, A; Schmid, M; Masson, S; McPherson, S
Abstract : Introduction: Chronic infection with hepatitis C (HCV) is a major cause of cirrhosis and hepatocellular carcinoma. Many patients are now eligible for oral direct acting antivirals (DAAs), with cure rates >90% possible. The main challenge for viral hepatitis teams now is to engage known HCV infected individuals in treatment, and to find undiagnosed cases. There are an estimated 2000 HCV infected individuals in North of Tyne (NOT) Region (Newcastle, North Tyneside and Northumberland). However, it is unknown what proportion of HCV infected individuals diagnosed in this region ultimately receive treatment. Aim: 1) To determine the proportion of HCV infected individuals in our region who were referred for treatment, received treatment and achieved a sustained virological response (SVR). 2) To determine whether contact can be made with patients who never had HCV RNA confirmatory testing, were never referred, or persistently missed clinic appointments. Methods: We conducted a retrospective review of all patients with a NEW positive HCV antibody test between Jan 2011 and Dec 2012 in the NOT region. Patients were identified from the North East Public Health Laboratory. Medical records and treatment databases were accessed to establish outcomes for all patients. For patients never referred or lost to follow up a letter was sent to their GP advising them to contact the patient and discuss re-referral. Results: Overall 92% of HCV antibody positive patients have HCV RNA testing performed (Figure 1 ). 88% of HCV RNA positive patients are referred for consideration for treatment. Of these, 47% commenced antiviral therapy, with an overall SVR of 66%. Persistent non-attendance was the main reason for not starting treatment. Letters were sent to GPs of 77 patients who were never referred or were lost to follow up. The GP response rate was 31% (24/77) after 8 weeks. Six (8%) patients were re-referred to the service. Conclusion: There is a high rate of referral for HCV RNA positive patients (88%) in the North of Tyne region, with 47% commencing PEG-IFN based treatment. Some reasons for not starting treatment should resolve in the DAA era, increasing treatment rates.Contacting GPs to re-refer known HCV RNA positive patients is an inexpensive approach, but resulted in relatively few referrals. Improving HCV testing across the region is essential to increase access to treatment. Disclosure of Interest: None Declared